(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2018)
هدف هذا البحث إلى دراسة مدى تأثير استخدام نظم المعلومات المحاسبيَّة في تحسين جودة القرارات الإداريَّة، وذلك في عيِّنة من المصارف العاملة في السَّاحل السُّوري. قام الباحثان بتوزيع (100) استبياناً على المديرين ورؤساء الأقسام والمراقبين وأفراد الكوادر الإداريَّة المسؤولة عن اتِّخاذ أشكال وأنواع مختلفة من القرارات المعتمد في اتِّخاذها على المعلومات المحاسبيَّة في المصارف محل الدراسة، وقد بلغ عدد الاستبانات المستردَّة والصَّالحة للتَّحليل والَّتي تمَّ تفريغها (77) استبانة. قام الباحثان بتحليل البيانات باستخدام برنامج التَّحليل الإحصائي (SPSS 20). وفي نهاية هذا البحث توصَّل الباحثان إلى مجموعة من الاستنتاجات، وأهمّها: يوجد تأثير معنوي لكلٍّ من المتطلَّبات المادِّيَّة والبرمجيَّة والبشريَّة والتنظيميَّة المتاحة لنظم المعلومات المحاسبيَّة، فضلاً عن اهتمام ومساندة الإدارة العليا لهذه النُّظم في تحسين جودة القرارات الإداريَّة في المصارف محل الدراسة. كما تقدَّم الباحثان بمجموعة من التَّوصيات، والَّتي كان أهمُّها: ضرورة توفير المستلزمات المادِّيَّة الخاصَّة بتشغيل نظم المعلومات المحاسبيَّة في المصارف عيِّنة الدِّراسة والمواكبة المستمرَّة للمستجدَّات التقنيَّة في هذا المجال، وأن تتناسب البرمجيَّات المستخدمة مع متطلَّبات الأعمال والوظائف في المصارف وضرورة التَّحديث المستمر لهذه البرمجيَّات بما يتناسب مع تطوُّر كيفيَّة أداء وإنجاز هذه الأعمال والوظائف، زيادة التَّنسيق بين جميع أقسام المصرف ودوائره، وزيادة مرونة الهيكل التَّنظيمي للمصرف. The purpose of this study is to examine the effect of the use of accounting information systems on improving the quality of administrative decisions in a sample of banks in the Syrian coast. The researchers distributed (100) questionnaires to managers, heads of departments, supervisors and administrative personnel responsible for taking various types of decisions adopted on the accounting information in the banks in question. The number of returned and valid questionnaires that were discharged was (77). The researchers analyzed the data using the Statistical Analysis Program (SPSS 20). The researchers conclude that there is a significant effect on the physical, software, human and organizational requirements of the accounting information systems, as well as there is a significant effect of the interest and support of the senior management of these systems to improve the quality of administrative decisions in the banks which is the research’ sample. The researchers recommend that there is a necessity of providing the material requirements for the operation of accounting information systems in the banks, which is the research’ sample and there is necessity to continuous updating of technical developments in this field. The software should be adapted to the business requirements and functions in the banks. The development of how to perform these functions, increase the coordination between all sections of the bank and its departments, and increase the flexibility of the organizational structure of the bank.